Isolation and Characterization of Chemical Constituents from the Roots of Silene viscidula Franch. - Liao1, Caili; Zhao1, Baosheng; Wang2, Xiao; Liu1, Chunsheng; Xu1, Guojie; Liu1, Siqi; Zhang1, Xiaoqin; Wang1, Xueyong (Asian Journal of Chemistry, 2013)
In the present study, eight compounds were isolated and characterized by alcohol extraction method from the roots of Silene viscidula Franch. These compounds were emodin (1), physcion (2), a-spinasterol (3), hexadecanoic acid (4), sinocrassuloside VI (5), sinocrassuloside VII (6), sinocrassuloside VIII (7) and sinocrassuloside IX (8). Among them, compounds 1, 2, 3 and 4 were isolated from the roots of Silene viscidula Franch for the first time and compounds 1, 2 and 4 were first reported from the genus of silene. The chemical compositions show that Silene viscidula had distantly related with its confused specie of Psammosilene tunicoides.